Validation of SICK score - A severity of illness scoring system at a tertiary care centre in Puducherry - Dr. Shivaramakrishna Babji.N.; Dr. Bala gopal. M; Dr. N Anoop Sharma; Dr. Chandran Sivaguru (Pediatric Review: International Journal of Pediatric Research, 2017)
Objectives: Validation of SICK score for its ability to predict out come. Validation based on predominant system involved. Methods: Prospective study done at tertiary care centre in puducherry. Inclusion criteria: All children admitted in PICU between 1 month & 12 year in 6 month period. Exclusion criteria: Patients with surgical illness, congenital anomalies, non availability of consent. Physical variables of Temperature, Heart Rate, Respiratory Rate, Blood pressure, Capiallary Refill time, Oxygen saturation & sensoriurn (using AVPU scale) were recorded at the time of admission. SICK score was calculated and outcome was recorded as survived or expired. Association of patients outcome with total score was done using logistic regression analysis. The receiver operating characteristic (ROC) curve analysis was performed to decide the optimum cut off point in terms of total score that provides maximum sensitivity & specificity. Area under ROC curve (AUC) was used to compare the predictive power of total score. All analysis was carried out using SPPS software version 13.0. Results: Total of 354 Children were analyzed. For SICK score of <1 mortality was 0%, which gradually increased to 100% with a score of 7 or more. The area under the ROC curve was 93% (95%: CI: 89.8% - 97.3%) indicating good predictive ability of the score. Conclusion: SICK score has good predictive ability and uses only physical criteria. Further SICK score is not influenced by predominant system involved.